Brassinosteroids Enhance Immunity Against Candidatus Liberibacter Asiaticus in Citrus Plants: A Promising Approach to Control Huanglongbing (HLB) - Aryal, Divya; Ben Abdallah, Saoussen; Pérez-Hedo, Mertixell; Urbaneja, Alberto; Alférez, Fernando (2024)
Citrus greening, also known as Huanglongbing (HLB), is a severe bacterial disease caused by Candidatus Liberibacter asiaticus and transmitted by the Asian citrus psyllid insect. This disease is a major threat to the citrus industry worldwide, leading to stunted tree growth, small and misshapen fruit, and eventually the death of the plant. The bacterium is injected into the phloem tissue of citrus plants by the psyllid insect during feeding, and causes a cascade of diverse adversal reactions, including phloem plugging and a burst in oxidative stress. Brassinosteroids (Brs) are a type of plant steroid hormone that regulates developmental processes throughout the plant life cycle. Recent studies have shown that Brs have potential in providing immunity against bacterial diseases in various plants. This study aimed to assess the effect of Brs application on the response of citrus plants, and also possible effects on psyllid biological cycle. Under controlled conditions in the greenhouse, young Valencia trees grafted on US-942 rootstock were maintained in mesh cages. After Br treatment, two couples of HLB+ psyllids per cage were introduced. We evaluated oviposition, nymph survival, bacteria titer, and immunity-related gene expression. The results showed that Brs induced immunity-related gene expression and significantly reduced psyllid infection, oviposition, and bacteria titer in the plants. These findings suggest that Brs have the potential to delay the progression of HLB and enhance the immunity in healthy citrus plants against the disease. Further research is needed to optimize the application of Brs and evaluate its effectiveness in larger-scale field trials.